Nonimmune hydrops foetalis (NIHF): value of fetal autopsy and comparison with ultrasound findings - G., Umamaheswari; T., Ramya; V., Chaitra (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Nonimmune hydrops foetalis (NIHF) is a terminal catastrophic event of pregnancy caused by numerous diverse etiology. The aim of this study was to assess the significance of foetal autopsy and to compare the prenatal ultrasound (USG) and foetal autopsy findings in cases of NIHF. Methods: All perinatal autopsies performed at the department of pathology between March 2011-February 2018 were retrospectively reviewed. Of the received 130 autopsies, twenty cases of NIHF were identified, records of which were collected and correlated with maternal medical history, prenatal imaging and autopsy findings. Results: The malformations with hydrops foetalis were classified according to the involved organ system. They were cardiothoracic (7/20 cases), genitourinary (3/20 cases), gastrointestinal lesions (1/20 cases), chromosomal (4/20 cases) and multisystem anomaly/syndromic association (5/20 cases). Complete agreement between USG and autopsy was seen in 8 (40%) cases. In 5 (25%) cases autopsy findings were in total disagreement with USG diagnosis. The rest of the 7 (35%) cases, autopsy revealed additional information and changed the recurrence risk in two cases. Conclusions: Present study demonstrates the high rate of discordancy between USG and autopsy examination in cases complicated by NIHF. Foetal autopsy confirms the USG findings (quality control/audit), adds additional findings or changes the final diagnosis, which helps in redefining the recurrence risk and plausible genetic counselling for future pregnancies. Hence present study underscores the need for autopsy in all cases of NIHF.